Ghost soldier eaudiobook - Maden, Mike (Oregon Files, 2024)
A deadly war game. An adversary as hard to find as he is to kill. Weapons so sophisticated, none have seen the like before. Juan Cabrillo and the crew of the Oregon have finally met their match in this pulse-pounding new adventure in the #1 New York Times bestselling series. When African jihadis attack a Nigerian regiment using American weapons, Cabrillo and the Oregon crew are on the case, investigating from Afghanistan to Kuala Lumpur to track a mysterious arms dealer—a genius, or perhaps a devil—known only as the Vendor. Cabrillo goes undercover to find the Vendor’s base, but his adversary isn’t just an arms smuggler. He’s an arms maker , and Cabrillo just walked into a lethal military game alongside the most dangerous mercenaries in the world, designed to test the Vendor’s cutting-edge AI arsenal. And yet, surviving an arena full of flame-throwing robots isn’t even his biggest problem. The Vendor has an army of high-speed drones headed for a pivotal military site, and if the Oregon crew can’t stop them from releasing a deadly neurotoxin, the entire globe will erupt in conflict.